Coumarin glycosides from Hydrangea paniculata slow down the progression of diabetic nephropathy by targeting Nrf2 anti-oxidation and smad2/3-mediated profibrosis - Sen, Zhang; Weida, Wang; Jie, Ma; Li, Sheng; Dongming, Zhang; Xiaoguang, Chen (Phytomedicine (Stuttgart), 2019)
Water extract of Hydrangea paniculata (HP) stem, rich in coumarin glycosides, has been demonstrated to have renal protective effect in several experimental kidney injury animal models. Currently, it is under pre-clinical development as a class 5 herbal drug against membranous nephropathy. However, whether it also benefits diabetic nephropathy (DN) is not clear. This study was performed to investigate the protective effect of HP on streptozotocin-induced experimental DN, and further understand its molecular mechanisms. In the present study, type 1 diabetes rat model was established by the intraperitoneal injection of streptozotocin. HP was orally administered every day for three months. Biochemical analysis and histopathological staining were conducted to evaluate the renal functions. In vivo pharmacokinetic study was conducted to analyse the metabolites of HP with high blood drug concentration. In vitro assay using these metabolites was performed to analyse their ability to reduce reactive oxygen species (ROS) production induced under high glucose (HG) condition by flow cytometry. Reverse transcription-polymerase chain reaction was conducted to analyse the mRNA level of nuclear factor (erythroid-derived 2)-like 2 (Nrf2) and IL6 and western blot was performed to analyse the phosphorylation status of smad 2/3 in HK2 cells under TGFβ1 stimulation. The treatment with HP significantly reduced the blood urea nitrogen and serum creatinine content, and urine albumin excretion in diabetic rats, and increased the creatinine clearance rate. Periodic acid-schiff and methenamine staining and immunohistochemistry revealed that HP also ameliorated glomerulosclerosis and tubular vacuolar degeneration, as well as the deposition of fibronectin and collagen IV in the glomeruli. Pharmacokinetic study results revealed that the major coumarin compounds from HP were metabolised into umbelliferone and esculetin. By in vitro assay, umbelliferone and esculetin were found to significantly decrease ROS production induced by HG content, as well as increase the mRNA level of Nrf2. HP and its metabolites also can down-regulate fibronectin secretion in HK2 cells stimulated by TGFβ1 and inhibit smad2/3 phosphorylation. HP has beneficial effect on DN by increasing Nrf2 expression and inhibiting TGF-smad signal activation. Further, it can be a novel herbal drug against DN. [Display omitted]